Writing Scripts for “Bincang Sore” Program Broadcasts on Radio Solopos 103 FM - Priliantini, Anjang; Ambarwati, Rista (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2024)
This research examines the process of preparing the Bincang Sore program script on Radio Solopos 104 FM, one of the most popular radio stations in Solo. This research uses broadcast strategy theory with qualitative research methods and participatory observation as primary data collection techniques. This research shows that broadcast scripts are a broadcast strategy that goes through three stages. First, pre-production, which includes efforts to understand the purpose of writing the script and the characteristics of the audience, researching to find ideas for script material followed by collecting related information, determining the structure of the script according to the duration of the program, as well as selecting style and language based on audience characteristics. Second, the production stage includes preparing an interesting opening speech, arranging the material by referring to everyday language, short, simple, and not long-winded, and choosing words that are easy to hear and understand by listeners and easy for the announcer to pronounce. During production, editing and revisions are also done if parts need to be corrected. Third, the post-production stage evaluates the Bincang Sore program broadcast script, rarely done at Solopos Radio.